Cyclization of a G4-specific peptide enhances its stability and G-quadruplex binding affinity - Ngo, Khac Huy (2022)
G-quadruplexes(G4) arenon-canonical nucleicacidstructures with important implications in biology. Based on an a-helical fragment of the RHAU helicase that displays high specificity for parallelstranded G-quadrplexes, herein we demonstrate its head-to-tail cyclization by a high-eﬃciency ligase. The cyclic peptide exhibits superior stability and binding aﬃnity to a G-quadruplex, and can serve as an excellent investigational tool for chemical biology applications